Lactobacillus rhamnosus ameliorates acne vulgaris in SD rats via changes in gut microbiota and associated tryptophan metabolism - Huang, Yukun; Huang, Yaxin; Xia, Dengmei; Liu, Lu; Xiong, Xia; Ouyang, Yongliang; Deng, Yongqiong (Frontiers in Immunology, 2024)
Background The depletion of beneficial bacteria in the gut has been found in patients with acne vulgaris, and in previous studies, the supplement of Lactobacillus rhamnosus led to the improvement of adult acne. Nevertheless, the potential mechanism of L. rhamnosus in the amelioration of acne vulgaris has not been elucidated yet. Methods To mimic the human intestinal environment, a pseudo-germ-free rat model was used, and then gut microbiota from healthy individuals and acne patients were transplanted into rats. The effects of L. rhamnosus and tryptophan (Trp) metabolites on a rat acne model were investigated by gavage. Then, 16S rRNA analysis and targeted measurement of metabolites were performed to discover the differences in gut microbiota and metabolites between groups. Finally, HaCaT cells pretreated with Cutibacterium acnes were employed to validate the effect and mechanism of Trp metabolites on acne. Results L. rhamnosus significantly improved acne-like symptoms in rats by suppressing the level of inflammatory cytokines such as IL-1β, IL-6, and TNF-α. L. rhamnosus induced an increase in the production of indole-3-acetic acid (IAA) and indole via targeted Trp metabolic analyses. Furthermore, L. rhamnosus promoted bacterial diversity and also enhanced the Firmicutes/Bacteroidota (F/B) ratio, which was positively related to both IAA and indole. Finally, the roles of IAA and indole in alleviating acne vulgaris were confirmed both in vitro and in vivo, which could be reversed by AhR inhibitors. Conclusion Our study demonstrated that L. rhamnosus could exert its therapeutic effects on acne vulgaris by modulating the gut microbiota and regulating associated Trp metabolites.